KINETICS OF THE OXIDATION OF VITAMIN C - Sitti Rahmawati; Bunbun Bundjali (Indonesian Journal of Chemistry, 2012)
Vitamin C or ascorbic acid is needed by the human body but it is already damaged by the rise in temperature due to be oxidized to L-dehydroascorbic acid. This research aims to determine the kinetics of oxidation of ascorbic acid due to an increase if temperature (40-80 °C) and to design an ascorbic acid oxidation reaction laboratory module to be applied in the senior high school reaction kinetics curriculum. The determination of the kinetics of the oxidation of ascorbic acid applies the integral and half-change time methods, while the concentration of the remained ascorbic acid in sixty minute intervals is determined by iodimetric titration method. Decomposition of ascorbic acid was measured at 40, 50, 60, 70 and 80 °C. The results of this research indicate that at 40, 50, 60, 70 and 80 °C the kinetics of the oxidation of ascorbic acid is a first-order reaction with rate constants of 4.55 x 10-4, 5.85 x 10-4, 8.4 x 10-4, 1.1 x 10-3 and 1.015 x 10-3 min-1, respectively. Pre-exponential factor or the frequency of collisions is a factor which is a measure of the collision rate. The activation energy and the pre-exponential factor for the oxidation of ascorbic acid were found to be 20.73 kJ.mol-1 and 1.372 min-1. The procedure used in this study was modified into a laboratory module will be applied in the teaching of reaction kinetics at the senior high school level.